Kontribusi Teori Belajar Robert Mills Gagne Dalam Meningkatkan Kompetensi Pedagogik Pendidik - Neffi Damayanti damayanti; Maulida Amelia Putri; Adinda Hafizah; Dinda Febriyanti Sinaga; Muhammad Alwi Batubara (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
One of the four qualities an educator must possess is teaching ability. The authors recognize the value of teaching competencies, their understanding and application, the challenges educators face in delivering instruction, and the responses to those challenges. This study attempts to explain how Gagne's learning theory can help teachers improve their teaching ability. This is a descriptive qualitative study. The methodology used was a literature review from numerous peer-reviewed scientific journals worldwide. The results of the discussion show that Perspective Learning Theory and Descriptive Learning Theory have been applied in applying Gagne's "Nine Events in Teaching" model. Keywords: Competence, pedagogic, learning theory, Gagne